Survey: Discovery in Wireless Sensor Networks - Valerie Galluzzi; Ted Herman (International Journal of Distributed Sensor Networks)
Neighbor discovery is a component of communication and access protocols for ad hoc networks. Wireless sensor networks often must operate under a more severe low-power regimen than do traditional ad hoc networks, notably by turning off radio for extended periods. Turning off a radio is problematic for neighbor discovery, and a balance is needed between adequate open communication for discovery and silence to conserve power. This paper surveys recent progress on the problems of neighbor discovery for wireless sensor networks. The basic ideas behind these protocols are explained, which include deterministic schedules of waking and sleeping, randomized schedules, and combinatorial methods to ensure discovery.